2003
DOI: 10.1097/01.tp.0000090868.88895.e0
|View full text |Cite
|
Sign up to set email alerts
|

Specific and durable elimination of antibody to donor HLA antigens in renal-transplant patients

Abstract: Plasmapheresis and low-dose CMV-Ig combined with traditional immunosuppression is effective in producing a specific and durable elimination of antibody to donor HLA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
130
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 23 publications
2
130
2
Order By: Relevance
“…Montgomery et al (25) followed up DSA of 49 kidney transplant recipients who underwent a desensitization protocol of PP/low-dosage IVIG and demonstrated that 63% lost DSA at the end of the treatment and 89% Ն2 mo after the end of treatment; however, the Mayo Clinic group showed that the majority of their desensitized patients continued to have low levels of DSA (26). In our study, 52% of patients lost DSA completely, and 30% lost some of their DSA or decreased DSA strength, indicating that both methods, high-dosage IVIG alone and PP/high-dosage IVIG, are effective in downregulating antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Montgomery et al (25) followed up DSA of 49 kidney transplant recipients who underwent a desensitization protocol of PP/low-dosage IVIG and demonstrated that 63% lost DSA at the end of the treatment and 89% Ն2 mo after the end of treatment; however, the Mayo Clinic group showed that the majority of their desensitized patients continued to have low levels of DSA (26). In our study, 52% of patients lost DSA completely, and 30% lost some of their DSA or decreased DSA strength, indicating that both methods, high-dosage IVIG alone and PP/high-dosage IVIG, are effective in downregulating antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Protocols that are similar to those used for treating AMR after transplantation also have proved useful in eliminating antibodies to donor HLA and ABO blood group antigens that existed before transplantation in sensitized patients, thereby allowing for successful transplantation of kidneys across these previously unscalable immunologic barriers (31,(35)(36)(37)(38)(39)(40). In biopsies of initially HLA-incompatible renal allografts, including biopsies that were performed for graft dysfunction and protocol biopsies of stably functioning grafts, we have found a strong association between PTC C4d staining and neutrophil margination, similar to findings in cases with a negative pretransplantation cross-match.…”
Section: C4d In Abo-incompatible Allografts: Rejection or Accommodation?mentioning
confidence: 99%
“…After then, it has been an established method to overcome such incompatibility in several centers around the world, and for these experienced centers, donor kidney exchange is a far more simple and easy method to overcome the incompatibility of DRP than other protocols, including plasmapheresis or immunoadsorption (15,16). Some centers are even using donor kidney exchange to find donors with lesser HLA mismatch (3,4).…”
Section: Discussionmentioning
confidence: 99%